Adaptation Strategy of the Bajo Fishermen towards Climate Change - Herdiansyah, Herdis; Ningrum, Zarah Beby; Fitri, Ika Syiami; Mulyawan, Mulyawan (Jurnal Bina Praja, 2018)
Climate change currently becomes the concern of policymakers and academics because the impact is already extensive. The Bajo People Community, located in Wakatobi, Southeast Sulawesi is a coastal community with a significant portion of its population living as fishermen. The people and fishermen in the Bajo people also felt the impact of climate change on the coastal and marine environment. The effect on the environment is very influential on the economic and social community of the Bajo People. This study aims to define the alternative to propose adaptation strategy to deal with climate change for fishermen. The benefit of this study is to provide input for planners, policymakers, and practitioners related to fisheries in the territory of Indonesia. Climate change adaptation is necessary to maintain the quality of life of fishers and to achieve the stability of available resources. This study used a literature study and Analytical Hierarchy Process (AHP) as its method to find the alternative strategy in order to face climate change. The plan proposed in this research are three, namely increasing knowledge and information about climate change, resource management, and livelihood diversification. The result of this research is that Bajo Fishermen need an appropriate adaptation strategy to mitigate the situation towards climate change issues, which is necessary to prevent the disruption of economic and social activities, focusing on the cognitive, practical and structured aspects that base on cultural values, norms, and customs of the Bajo people. This study found four useful variables to be used as coping strategies for climate change, which are social, ecological, economic and political alternatives. The four variables are strengthening the surveillance of epidemic disease, developing fish gear technology, improving proper water treatment management, and creating awareness of climate change for the fishermen community.